Faktor Determinan Hiperurisemia pada Lansia - Alfi Syahar Yakub; Muhammad Nur; Muhammad Asikin (Celebes Advance Health Journal, 2026)
Hyperuricemia is a metabolic disorder that often occurs in the elderly and can progress to gout and other metabolic complications. Many older adults are unaware of their elevated uric acid levels because symptoms often appear at a later stage. Health education and uric acid level testing are important strategies to increase public awareness and support early detection.Objective: This study aims to analyze the increase in knowledge and support early detection of hyperuricemia through educational activities and examination of uric acid levels in the elderly.Methods: The study used a cross-sectional design in a community service activity carried out in Sudiang Raya Village, Makassar City in December 2025. A sample of 35 elderly people was selected using a purposive sampling technique. Data were collected through a knowledge questionnaire and uric acid level examination. Data analysis was performed using univariate, bivariate, and multivariate methods using logistic regression. Results: Health education significantly increased the knowledge level of older adults. High-purine food consumption, body mass index, and a history of hyperuricemia were associated with increased uric acid levels. Conclusions: Health education and uric acid examinations are effective in increasing knowledge and supporting early detection of hyperuricemia in the elderly in the community.